2009
DOI: 10.4021/jocmr2009.06.1242
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exclusive Breastfeeding in South Gujarat Region of India

Abstract: ObjectiveTo estimate the situation of breastfeeding in Surat among infants and to determine variables associated to major risks for early weaning.Design and settingsMothers coming to the well baby clinic for immunization of infants at Government Medical College and Hospital were interviewed using pretested questionnaire.SubjectsMothers with their infants who have not completed one year of age.MethodsIn this cross sectional study, 498 mothers were selected for study from May to September, 2008. Survival analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 8 publications
8
29
4
Order By: Relevance
“…Chudasama et al reported prevalence of EBF to be 37% in Gujrat, India [24]. Another study from India among rural women in Tamil Nadu showed the prevalence to be 34% [25] which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…Chudasama et al reported prevalence of EBF to be 37% in Gujrat, India [24]. Another study from India among rural women in Tamil Nadu showed the prevalence to be 34% [25] which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, it has been found that maternal age less than 20 years can increase the risk of early weaning by 6 times. 33 Lower maternal education level has been identified as a potential risk factor to interrupt the EBF. 34 The mothers, who are employed, would have inadequate time for baby care and usually are separated from their children during working hours; therefore, working commitment can disrupt EBF.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been previously reported in India. 33 The potential explanation may be related to insufficient knowledge and skills for proper breastfeeding, as well as the misperception that the EBF may have unfavorable effects on the physical fitness and postpartum recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It is a complex procedure involving both the psychological and physiological processes which in turn is governed by a lot of social, economic and other cultural factors (Figure 1). These factors affect breastfeeding and exclusive breastfeeding in different directions and to varying degrees depending on culture [36][37][38][39][40].…”
Section: Conceptual Frame Workmentioning
confidence: 99%